The Influence of Company Performance on Audit Delay with Public Accounting Firm Quality as the Moderating Variable - Evani, Elsa Saphira; Susilowati, Dewi; Kusumastati, Widyahayu Warmmeswara (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
This research aims to find the influence of company performance on audit delay with public accounting firm quality as the moderating variable. Sample used are consumer goods sector companies that have been listed on the IDX from 2019 to 2020. Data are data from 70 companies listed on Indonesia Stock Exchange. The results of this study indicate that: profitability has a significant negative effect on audit delay, solvency has a significant negative effect on audit delay, quality of Public Accounting Firms cannot moderate the effect of profitability on audit delay, and quality of Public Accounting Firms cannot moderate the effect of solvency on audit delay.